On a sequence involving products of primes. Issue 6 (18th August 2022) - Farhadian, Reza; Jakimczuk, Rafael
Abstract: For n ∈ {1, 2, 3 … } let pn # be the product of the first n prime numbers, which is called the n th primorial. It is well-known that . In this note, we obtain some asymptotic expansions for the sequence, and we also study the asymptotic behavior of some related sequences. Furthermore, we establish a generalization of the limit formula .